Compact planar array antenna with electrically beam steering from backfire to endfire based on liquid crystal. Issue 7 (20th March 2018) - Ma, Shuang; Zhang, Shao‐Qing; Ma, Lei‐Qiang; Meng, Fan‐Yi; Erni, Daniel; Zhu, Lei; Fu, Jia‐Hui; Wu, Qun
Abstract : In this study, a novel electrically steerable planar array antenna based on liquid crystal (LC) is elaborately designed, fabricated and measured. The occupied area and undesired coupling of the meander line phase shifter are reduced by chamfering appropriately. Combined with the electrically tunable LC material, the miniaturised phase shifter achieves 146° phase shift and 122.7°/dB frequency‐dependent figure‐of‐merit. Utilising in series phase shifters, power dividers and in parallel patches, the proposed antenna features compact configuration 41° continuous wide beam scanning range from forward to backward at the satellite communication band 12.5 GHz. At the same time, it maintains satisfactory reflection coefficient and impedance bandwidth at each angle. Finally, the measurements validate the scanning of the beam by electrically tuning the phase shift between the radiating elements.